Penerapan Media KomunikasiLife-Sized-Game "Postcov" Pada TK Tunas Islam Semarang - Mukaromah Mukaromah; Dzuha Yanuarsari (ABDIMASKU : JURNAL PENGABDIAN MASYARAKAT, 2024)
Knowledge is one of the needs in education. Kindergarten Doa Ibu Semarang is an educational park that has problems related to the direct practice-based learning model which makes it easier for children to understand communication messages in the form of knowledge provided. So far, this school has not had any unique educational media that can provide learning to children through the process of learning while playing. The existing media is still in the form of practical media that are often found in other schools. Meanwhile, after the Covid-19 pandemic, memories still remain to provide lessons to be alert regarding pandemics and health themes. Through understanding and providing knowledge from an early age, it will have a good impact on preventing pandemics or diseases in the future. So there is a need for creative, educational media that can provide the development of learning concepts at Tunas Islam Kindergarten Semarang. This educational media in the form of a life-sized game with the name "Postcov" is the result of a research project by the implementing team as a new form of media which is expected to provide refreshment to the learning concept. The activities are carried out using the learning while playing method so that students increase their enthusiasm in absorbing the material while playing on game media. The final result of carrying out this service activity is to test the extent to which the "Poscov" learning media can be implemented with students at the Tunas Islam Kindergarten, Semarang.